Study and optimization of aroma recovery from beer by pervaporation - Margarida Catarino (2009)
This work studies the aroma extraction from beer by pervaporation, using a polyoctylmethylsiloxane/polyetherimide (POMS/PEI) composite asymmetric membrane. A response surface methodology (RSM) was used to describe the influence of the operating conditions (factors) on process performance. The factors considered for the design of experiments were the feed temperature, the feed velocity and the permeate pressure. The responses considered were the permeate flux, the aromas/ethanol selectivities, the ethanol concentration and the ratio between high alcohols and esters concentrations on the permeate. It was concluded that the membrane flux increases with the temperature and cross feed velocity while it decreases with permeate pressure. The aroma selectivities are affected by the operating conditions according to their nature. RSM methods generated interpolating polynomial models that describe the relationship between the operating conditions and process responses. A good agreement between experimental and predicted values was observed. The optimal operating conditions were achieved using an objective function that weights the selected responses desirability. The optimal operating conditions were 112.4 degrees C for feed temperature, 0.45 m s(-1) for feed velocity and 1.0 mbara for permeate pressure. For these conditions the permeate flux was predicted to be 7.26 kg m(-2) s(-1); the high alcohols selectivity ranged from 1.31 to 3.39; the esters selectivity ranged from 14,46 to 17.10 and the high alcohols/esters ratio was predicted to be 1.07. Experimental results for the runs performed at the optimal operating conditions mostly agreed with the predicted values. (C) 2009 Published by Elsevier B.V.